Sosialisasi Pengadaan Tanah untuk Tempat Penampungan Sementara dan Tempat Pembuangan Akhir Sampah Terpadu Dinas Lingkungan Hidup Kota Banjarbaru - Zainal Aqli; Alamsyah; Andi Erwin Nurba; Fadhilla Asyri (Arsil Media, 2023)
Land acquisition has been regulated through Law Number 2 of 2012 concerning land acquisition for development in the public interest, and Presidential Regulation Number 71 of 2012 concerning the implementation of land acquisition for development in the public interest, as well as Regulation of the Head of the National Land Agency number 5 of 2012 concerning technical guidelines for the implementation of land acquisition. The purpose of this community service is to increase the understanding and knowledge of regional heads, local government agencies, and especially the community about land acquisition for Temporary Shelters and Integrated Waste Disposal Sites of the Banjarbaru City Environmental Service. The specific target of this community service is for regional heads, local government agencies, and especially the community to know the regulations or policies in the land acquisition mechanism as well as the process of valuation and calculation of Fair Replacement Value or Market Value in Banjarbaru City, South Kalimantan Province. Community service activities carried out by the team by educating the process and stages of land acquisition according to regulations for Temporary Shelters and Integrated Waste Disposal Sites of the Banjarbaru City Environmental Service have received a positive response. In socialization, the Government and the private sector are asked to work together to create and develop an environment for land acquisition for temporary shelters and integrated landfills that allow for private sector growth. Meanwhile, the community includes the participation of stakeholders and beneficiaries of development policies.